ENTRAI - Encontro das Tradições Italianas : festa popular : patrimônio cultural, lazer e turismo - Silva, Mauro Amancio da (My University, 2014)
The aim of this study was to investigate a popular carnival called Entrai - an Italian Traditions Celebration that takes place where the Italian immigration started in the mountains of the Rio Grande do Sul state Nova Milano, Farroupilhas district. First, the theme was chosen because there are no scientific writings on the event, and on the other hand, for its importance that allowed me to study some pertinent questions about leisure and tourism, which are areas that have always been related. The investigation was proposed to verify the purpose of the Entrai s creation, describe and analyze its characteristics, check out the tourists profile that are attracted to it and describe the innovations and peculiarities on the celebration s program in a critical way. The theoretical references are fundamentally based on leisure, carnivals and events as ways to attract tourists. This is a qualitative study and the methodology used is descriptive, a case study research. Document analysis, interviews, observations and field notes were used to collect information. The document analysis and the interviews were the strategies that allowed a better comprehension on the carnival s history and the understanding of its initial and current purposes. Our conclusions say that Entrai was created as part of a project of Farroupilha s municipal planning for tourism, with an objective to be a tourist and cultural attraction. This study also revealed that this event has a tourist potential, even though there are planning and management distortions that get out of the way with its initial purposes. The Entrai reveals itself as a popular carnival, which happens in an open space that must be preserved and prioritized by the city government, because of the historical relevance of the people that first arrived at the place.
O trabalho teve como objetivo investigar a festa popular de rua denominada Encontro das Tradições Italianas - Entrai, que ocorre no berço da imigração italiana na Serra Gaúcha Nova Milano, distrito de Farroupilha. Por um lado, a escolha do tema de investigação foi motivada pela inexistência de registros científicos sobre o evento, por outro, pela relevância do evento que permitiu estudar questões pertinentes ao lazer e ao turismo, áreas de estudo que sempre estiveram imbricadas. A investigação se propôs verificar as finalidades da criação do Entrai, descrever e analisar as características do evento, averiguar o perfil de turistas que a festa atrai e descrever criticamente as inovações e peculiaridades na programação da festa. O referencial teórico está centrado fundamentalmente nas questões pertinentes ao lazer, as festas populares e eventos como atração turística. O estudo é de corte qualitativo e a metodologia descritiva do tipo estudo de caso. Utilizou-se análise documental, entrevistas, observações e notas de campo como estratégia de coleta de informações do estudo. A análise documental e as entrevistas foram as estratégias que permitiram melhor compreensão sobre a história da festa e a análise de seus propósitos iniciais e atuais. As conclusões do estudo apontam que o Entrai nasceu como parte de um projeto de planejamento municipal do turismo de Farroupilha, onde o objetivo do evento era tornar-se atrativo turístico e cultural. O estudo também revelou que o evento tem um potencial turístico, embora apresente distorções de planejamento e gestão que desfiguram os propósitos para o qual foi criado. O Entrai revela-se como uma festa popular de rua, que ocorre num espaço aberto que deve ser preservada e priorizada pelo Poder Público do município de Farroupilha/RS, face à relevância histórica dos colonizadores da região.
Keywords: Turismo; Lazer; Evento turístico; Festa popular; ENTRAI - Encontro das Tradições Italianas; Turismo cultural; Tourism; Leisure; Touristic event; Carnival; Cultural tourism